Art et nation en Grande-Bretagne : contexte et histoire d’un lien privilégié - Michel Baridon; Frédéric Ogee (Revue Française de Civilisation Britannique)
In the history of Europe, the eighteenth century is often considered as the period of British supremacy. The Glorious Revolution (1688) had driven James II from the throne, putting an end to absolute and hereditary monarchy by divine right, replacing it by a constitutional monarchy in which the ultimate power lay in the hands of Parliament. That political progress was completed by religious freedom and economic prosperity, giving birth to a feeling of national pride, embodied by the emblematic figures of Britannia, John Bull in literature, and the national anthem, Rule Britannia, written by James Thomson and set to music by Thomas Arne. This feeling of national pride can be found in the development of an ‘English school of painting’, with the foundation of the Royal Academy of Arts in 1768. It was the outcome of an evolution that characterised the 1740s – decennium mirabile – by the convergence between the basic ideals of the nation and the new forms of artistic expression: the novel, landscape gardening and painting. A new wealthy public enjoyed the exhibitions organised by the Royal Academy and the works displayed thanks to the art market. What connection is there between this art and the British psyche? The answer to that question raises the issue of ‘the Englishness of English art’, of the link between the British nation and its art in the eighteenth century.